Association of cardiometabolic microRNAs with COVID-19 severity and mortality. Issue 2 (10th November 2021) - Gutmann, Clemens; Khamina, Kseniya; Theofilatos, Konstantinos; Diendorfer, Andreas B; Burnap, Sean A; Nabeebaccus, Adam; Fish, Matthew; McPhail, Mark J W; O'Gallagher, Kevin; Schmidt, Lukas E; Cassel, Christian; Auzinger, Georg; et al.
Abstract: Aims: Coronavirus disease 2019 (COVID-19) can lead to multiorgan damage. MicroRNAs (miRNAs) in blood reflect cell activation and tissue injury. We aimed to determine the association of circulating miRNAs with COVID-19 severity and 28 day intensive care unit (ICU) mortality. Methods and results: We performed RNA-Seq in plasma of healthy controls ( n  =   11), non-severe ( n  =   18), and severe ( n  =   18) COVID-19 patients and selected 14 miRNAs according to cell- and tissue origin for measurement by reverse transcription quantitative polymerase chain reaction (RT–qPCR) in a separate cohort of mild ( n  =   6), moderate ( n  =   39), and severe ( n  =   16) patients. Candidates were then measured by RT–qPCR in longitudinal samples of ICU COVID-19 patients ( n  =   240 samples from n  =   65 patients). A total of 60 miRNAs, including platelet-, endothelial-, hepatocyte-, and cardiomyocyte-derived miRNAs, were differentially expressed depending on severity, with increased miR-133a and reduced miR-122 also being associated with 28 day mortality. We leveraged mass spectrometry-based proteomics data for corresponding protein trajectories. Myocyte-derived (myomiR) miR-133a was inversely associated with neutrophil counts and positively with proteins related to neutrophil degranulation, such as myeloperoxidase. In contrast, levels of hepatocyte-derived miR-122 correlated to liver parameters and to liver-derived positive (inverse association) and negative acute phase proteins (positive association). Finally, we compared miRNAs to established markers of COVID-19 severity and outcome, i.e. SARS-CoV-2 RNAemia, age, BMI, D-dimer, and troponin. Whilst RNAemia, age and troponin were better predictors of mortality, miR-133a and miR-122 showed superior classification performance for severity. In binary and triplet combinations, miRNAs improved classification performance of established markers for severity and mortality. Conclusion: Circulating miRNAs of different tissue origin, including several known cardiometabolic biomarkers, rise with COVID-19 severity. MyomiR miR-133a and liver-derived miR-122 also relate to 28 day mortality. MiR-133a reflects inflammation-induced myocyte damage, whilst miR-122 reflects the hepatic acute phase response. Graphical Abstract: